Pendekatan Pemandangan Realistik dengan Menggunakan Digital Matte Painting - Satrya Mahardhika (Bina Nusantara University, 2011)
Movie is one entertainment that is favored by most people. Scenery appearance and spectacular shoots made movie needs high budget for the production. There are shoots looking difficult and needing extra efforts, but obviously it could be solved by using latest technology. Such technology is a combination of 3D and digital painting or image so it could bring digital painting alive: matte painting, a breakthrough in visual effects and movie. The research is conducted through exploration from manipulated images, references and retrieved real images in the specific place. Camera movement is also an important frame to define how far the image will be seen in the camera. So, when it is applied, it has no images that less-showed in camera framing. Although it has limitation in 2D images taken from limited frame, digital matte painting is able to answer industry needs in entertainment to create things that look real.